L’invenzione dell’America e l’esigenza di narrare nelle cronache delle Indie - N. Bravi, Adrián (TransCulturale, 2023)
The discovery of America and the testimonies narrated since its inception were two events born together. One would not existed without the other. A thirth element could not exist separately: the creative and immaginary reports of the chroniclers. The voyage of conquest of America is largely composed by narrative and imperial gaze of the chronicle. In this framework, the article analyzes the inseparability between discovery, testimony and narrative invention (that includes imagination too) as components that converge to build a new reality. This construction had a great impact on the theoretical definition of the features of twentieth-century Latin American literature. Invention, revision, and reconstruction of the discovery of America are historical and cultural items that resurface constantly in Latin American literature. Despite all that, novel was the only literary genre that failed to take root in the New World for three hundred years, it succeeded only after the nineteenth century.